Sosialisasi Pembayaran Iuran dan Monitoring SiWarga Berbasis Teknologi pada Perumahan Griya Pesona Asri Surabaya - Hariadi Yutanto; Ellen Theresia Sihotang; Putri Wulanditya; Pepie Diptyana (University of Merdeka Malang, 2020)
Griya Pesona Asri (GPA) is a residence which located in the northern part of Surabaya City. The specific location is in Medokan Ayu, Rungkut District. Since 2019, this residence has been used SiWarga electronic application to improve citizen administration. In the beginning 2020, the leader of RT 04 RW 10, designed an electronic citizen financial system as the development of SiWarga GPA that has been successfully used for data collection of local residents. Some of partner problems are financial management transparently; non-cash payment system to facilitate citizen’s fee transactions; reduce citizens risk overdue arrears. In relation with these partner problems, some activities that have been carried out begins with discussion housing residents and management, followed by the management and development of non-cash payment system features until socialization the operating system. A number of RT managers have mastered to use several, they have been quite proficient and enthusiastic. The residents have been able to monitor a number of arrears in payment. Administrators of RT no longer need to collect money. The administrators have also been able to know the total expenditure and income so that it can be used for the cash budgeting.DOI: https://doi.org/10.26905/abdimas.v5i2.4347